2011
DOI: 10.4081/cp.2011.e22
|View full text |Cite
|
Sign up to set email alerts
|

Significant Stenoses of Twin Circumflex Arteries Accompanied by Heart Failure: A Rare Coronary Artery Anomaly

Abstract: Although coronary artery anomalies may cause some clinical symptoms, most are incidentally discovered as benign findings on coronary angiograms. A circumflex coronary artery anomalously originating from the right sinus of Valsalva is the most common coronary anomaly. However, a double circumflex coronary artery, both stenotic in their mid portions, resulting in symptomatic heart failure is a rare clinical and angiographic condition. In this case, we present a 71-year-old male patient admitted to our clinic wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Although the anomalous origin of LCX has been described to be one of the most common congenital anomalies in many large angiographic series [3][4], the occurrence of double or twin Cx coronary arteries has been reported very rarely in the literature [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. In most of the reported cases of double Cx arteries, one Cx artery (LCX) had its origin from the left main artery while the other (RCX) had its origin from the right coronary sinus or the RCA [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. A similar finding was seen in our case with the LCX arising from the left main and the RCX arising from the ostio-proximal part of the RCA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the anomalous origin of LCX has been described to be one of the most common congenital anomalies in many large angiographic series [3][4], the occurrence of double or twin Cx coronary arteries has been reported very rarely in the literature [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. In most of the reported cases of double Cx arteries, one Cx artery (LCX) had its origin from the left main artery while the other (RCX) had its origin from the right coronary sinus or the RCA [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. A similar finding was seen in our case with the LCX arising from the left main and the RCX arising from the ostio-proximal part of the RCA.…”
Section: Discussionmentioning
confidence: 99%
“…An anomalous circumflex (Cx) coronary artery arising from the right coronary sinus or the right coronary artery (RCA) is one of the most frequent coronary anomalies, seen in 34.4-57.9% of the patients with coronary anomalies [3,4]. Double Cx coronary arteries, with one originating from the left system and the other from the right system, is an exceptionally rare coronary anomaly that has been reported only a few times in the literature worldwide [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. We present a case of double Cx arteries in a middle-aged male with acute myocardial infarction (MI), and its successful management using percutaneous coronary intervention (PCI) of the diseased right Cx artery (RCX).…”
Section: Introductionmentioning
confidence: 99%
“…Although most of them have no clinical significance, they may cause acute myocardial damage and/or chronic injuries in the area supplied by the anomalous coronary artery arising from the incorrect coronary sinus of Valsalva [ 5 ]. Some coronary artery anomalies may cause chest pain, arrhythmia, heart failure and sudden death [ 6 ]. Myocardial ischemia can occur because of earlier and more aggressive atherosclerosis compared to a normal coronary artery [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere, Karabay et al presented a case of twin Cx arteries arising from the left and right coronary systems with acute inferior myocardial infarction treated via percutaneous coronary intervention [ 5 ]. In a study by Cicek et al there were significant stenoses at both of the twin Cx arteries, leading to heart failure [ 17 ]. Andreou et al reported a case for preoperative identification of this anomaly in patients undergoing aortic valve surgery [ 18 ].…”
Section: Discussionmentioning
confidence: 99%